Silenced in the library - Jarvis, Zeke (Greenwood, an imprint of ABC-CLIO, LLC, 2017)
Alphabetical list of titles – Alphabetical list of authors – Topical guide to titles – Preface – Introduction – Race and censorship in America – Religion and censorship in America – Sex and censorship in America – Sexual orientation and censorship in America – Drugs and alcohol and censorship in America – Bad behavior and censorship in America – Graphic novels and censorship in America
Includes bibliographical references (pages 277-280) and index
Keywords: Challenged books; Prohibited books; Libraries; Censorship; American literature; Literature and society